2006
DOI: 10.1093/jac/dkl327
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nosocomial infections due to Pseudomonas aeruginosa producing metallo- -lactamase in two tertiary-care teaching hospitals

Abstract: beta-Lactam exposure is an important risk factor for MBL-PA infections even in a setting where patient-to-patient transmission plays a major role in the spread of the isolates. Other risk factors deserve further investigation, particularly exposure to fluoroquinolones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
27
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 14 publications
5
27
1
1
Order By: Relevance
“…The higher prevalence of resistance to cefepime, ceftazidime, ciprofl oxacin, meropenem, amikacin, gentamicin, and piperacillin/ tazobactam observed in the MPPa group is consistent with the results of Machado et al 5 and Zavascki et al 7 ; however, resistance in the NPPa group for our study was higher than the values reported by these authors. Normally, P. aeruginosa isolates are resistant to β-lactam antibiotics because of the hyperproduction of AmpC β-lactamase.…”
supporting
confidence: 92%
“…The higher prevalence of resistance to cefepime, ceftazidime, ciprofl oxacin, meropenem, amikacin, gentamicin, and piperacillin/ tazobactam observed in the MPPa group is consistent with the results of Machado et al 5 and Zavascki et al 7 ; however, resistance in the NPPa group for our study was higher than the values reported by these authors. Normally, P. aeruginosa isolates are resistant to β-lactam antibiotics because of the hyperproduction of AmpC β-lactamase.…”
supporting
confidence: 92%
“…To date, our understanding of the epidemiology of MBLproducing P. aeruginosa isolates is limited to outbreaks and infections reported from tertiary care medical centers (8,9,11,12,14,15,24,29). The occurrence of community-onset infections by MBL-producing P. aeruginosa has not been previously recognized, and the epidemiology of these infections outside hospitals has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified the risk factors for MBL acquisition (8,14,29) as well as the outcome of P. aeruginosa infections caused by MBL producers (12,14). The increasing prevalence of nosocomial infections produced by MBL-possessing P. aeruginosa strains severely compromises the selection of appropriate treatments and is therefore associated with significant morbidity and mortality.…”
mentioning
confidence: 99%
“…Risk factors associated with infections by MBL-producing P. aeruginosa isolates include recent use of ␤-lactams or fluoroquinolones, renal failure, indwelling urinary catheters, neurological disease, antineoplastic chemotherapy, corticosteroid therapy, and/or intensive care unit stay (14,47).…”
mentioning
confidence: 99%